Growth in infancy, infant feeding, childhood living conditions, and Helicobacter pylori infection at age 70. Issue 4 (1st October 1997) - Fall, C H D; Goggin, P M; Hawtin, P; Fine, D; Duggleby, S
Abstract : AIM: To examine childhood correlates of Helicobacter pylori infection in adults. DESIGN: Follow up study of men and women whose birth weight, weight at age 1 year, and feeding in infancy were recorded by health visitors. Data on childhood housing conditions were obtained by recall. SUBJECTS: 631 men and 389 women born in Hertfordshire during 1920–30 and still living in the east or northwest districts of the county. MAIN OUTCOME MEASURES: Serum H pylori IgG antibodies measured by enzyme linked immunosorbent assay. RESULTS: Independent of their current social class, subjects were more likely to be H pylori seropositive if they had large numbers of siblings (p < 0.0001), and if they had lived in a crowded house (p = 0.001), or shared a bedroom or bed in childhood (p = 0.02). Low weight at 1 year was associated with increased seropositivity rates in men (p = 0.0002), but not women (p = 0.8). Men and women who were breast fed in infancy were less likely to be seropositive than those who were bottle fed (p = 0.08). CONCLUSIONS: The findings support the current view that H pylori infection is often acquired in childhood by close person to person contact, and persists into adult life. H pylori infection may be a cause of failure to thrive in infancy, especially in boys. Alternatively, small infants may be more susceptible to infection. Breast feeding may prevent early infection.